Photoprotection. Recommendations of the Polish Dermatological Society. Part 1: Ultraviolet radiation and sunscreens - Narbutt, Joanna; Wolska, Hanna; Kaszuba, Andrzej; Langner, Andrzej; Lesiak, Aleksandra; Maj, Joanna; Placek, Waldemar; Reich, Adam; Rudnicka, Lidia; Zegarska, Barbara (Dermatology Review/Przegląd Dermatologiczny, 2018)
Ultraviolet radiation (UVR) is one of the components emitting from solar light and includes three wavelengths, i.e.: UVC, UVB and UVA. The unique biological properties of UVR and its huge influence on skin result in its role in development of various significant processes such as skin photoaging and development of precancerous skin lesions as well as skin neoplasms. Thus, there is an urgent need to use photoprotection, not only under excessive exposure to sunlight but as well as in everyday life. Recommendations of Polish Dermatological Society discuss properties of UVR, available sunscreens, their safety and efficacy. Controversies regarding their possible allergic potential and influence on vitamin Dsynthesis are highlitened. The sunscreen use in special populations such as children and non-immunononcompetent patients were also discussed. The recommendations refer to on European guidelines as well as on the experts’ knowledge and experience.